2010
DOI: 10.1136/jcp.2009.067264
|View full text |Cite
|
Sign up to set email alerts
|

Primary localised pleural neurofibroma: expanding the spectrum of spindle cell tumours of the pleura

Abstract: To the best of the authors' knowledge, localised neurofibromas have not been previously reported within the pleura. The presence of a bland spindle cell pleural neoplasm immunoreactive for CD34 may potentially be mistaken for a solitary fibrous tumour. While distinction is usually achieved on close attention to the histological features, staining with S100 protein, especially in small biopsies, should be considered to exclude a neurofibroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In NF1, the thorax and lungs can be affected in several ways, given the dense distribution of peripheral nerves throughout the thorax: cutaneous and subcutaneous neurofibromas on the chest wall and chest wall deformities; kyphoscoliosis; ribbon deformity of the ribs; thoracic neoplasms; parenchymal neurogenetic tumors [29-31]; and other respiratory manifestations that severely impair pulmonary function, such as upper airway obstruction by neurofibromas, central hypoventilation, diaphragm paralysis, diffuse and interstitial lung disease, and primary pulmonary hypertension [32-35]. …”
Section: Discussionmentioning
confidence: 99%
“…In NF1, the thorax and lungs can be affected in several ways, given the dense distribution of peripheral nerves throughout the thorax: cutaneous and subcutaneous neurofibromas on the chest wall and chest wall deformities; kyphoscoliosis; ribbon deformity of the ribs; thoracic neoplasms; parenchymal neurogenetic tumors [29-31]; and other respiratory manifestations that severely impair pulmonary function, such as upper airway obstruction by neurofibromas, central hypoventilation, diaphragm paralysis, diffuse and interstitial lung disease, and primary pulmonary hypertension [32-35]. …”
Section: Discussionmentioning
confidence: 99%
“…Langman et al [ 5 ] reported two cases of primary localized pleural neurofibroma out of which one was a known case of neurofibromatosis type I. Krishnamurthy et al [ 6 ], reported another case of isolated pleural neurofibroma in a 39-year-old female who presented with worsening chest pain. Another case of a 31-year-old male with pleural neurofibroma was reported by Gupta et al [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pleural involvement by neurofibroma is exceedingly rare with only three cases reported so far [12, 13]. Of these, only one case reported by Langman et al, was not associated with neurofibromatosis [13]. Primary pleural neurofibromas arise directly from intercostal nerves and form pleural based masses.…”
Section: Discussionmentioning
confidence: 99%